Modern Buddhist conjunctures in Myanmar : cultural narratives, colonial legacies, and civil society - Schober, Juliane (University of Hawaiʻi Press, 2011)
For centuries, Burmese have looked to the authority of their religious tradition, Theravada Buddhism, to negotiate social and political hierarchies. Modern Buddhist Conjunctures in Myanmar examines those moments in the modern history of this Southeast Asian country when religion, culture, and politics converge to chart new directions. Arguing against Max Weber's characterization of Buddhism as other-worldly and divorced from politics, this study shows that Buddhist practice necessitates public validation within an economy of merit in which moral action earns future rewards. The intervention of colonial modernity in traditional Burmese Buddhist worldviews has created conjunctures at which public concerns critical to the nation's future are reinterpreted in light of a Buddhist paradigm of power. Author Juliane Schober begins by focusing on the public role of Buddhist practice and the ways in which precolonial Buddhist hegemonies were negotiated. Her discussion then traces the emergence of modern Buddhist communities through the colonial experience: the disruption of traditional paradigms of hegemony and governance, the introduction of new and secular venues to power, modern concerns like nationalism, education, the public place of religion, the power of the state, and Buddhist resistance to the center. The continuing discourse and cultural negotiation of these themes draw Buddhist communities into political arenas, either to legitimate political power or to resist it on moral grounds. The book concludes with an examination of the way in which Buddhist resistance in 2007, known in the West as the Saffron Revolution, was subjugated by military secularism and the transnational pressures of a global economy. A skillfully crafted work of scholarship, Modern Buddhist Conjunctures in Myanmar will be welcomed by students of Theravada Buddhism and Burma/Myanmar, readers of anthropology, history of religions, politics, and colonial studies of modern Southeast Asia, and scholars of religious and political practice in modern national contexts.